An actual thermal efficiency expression for heat engines: Effect of heat transfer roadmaps. (October 2017) - Xu, Jinliang; Zheng, Yawen; Wang, Yanjuan; Yang, Xufei; Yu, Chao; Xie, Xuewang; Li, Zhi; Zhao, Xiaoli
Highlights: Connection between heat load and loss of energy quality was established. Actual thermal efficiency is Carnot efficiency multiplying by a coefficient. The coefficient is linearly related to a heating to cooling resistance ratio. Heat transfer roadmaps are critical to affect cycle performance. The theory provides general guidance for energy conversion systems. Abstract: In the framework of modern thermodynamics, "thermodynamics flow" and "thermodynamics force" are introduced to develop a real thermal efficiency expression for heat engine, which receives heat from a heat source and dissipates heat to environment to yield a work output, for the first time. Enclosed area of T-Q curves of a counter-current heat exchanger is the dissipation for heat to power conversion, representing loss of thermal energy quality. The relationship between heat load and dissipation for heat to power conversion is quantified. Such connection is written for both heating and cooling processes. Linking the thermal couplings between heating and cooling processes yields the thermal efficiency expressed as η real = C η Carnot, where C = 1 η Carnot - R 1 - η Carnot, η Carnot is the Carnot efficiency, R  =  R h / R c is the ratio of resistance in heating process R h divided by that in cooling process R c . The thermal efficiency theory tells us that no matter how complex a heat engine is, the engine should reach a lower resistance ratio of heating process with respect to cooling process to raise its thermal efficiency. The guidelines for design and operation of general heat engines are provided. A link between heat transfer and thermodynamics is presented in this work. As an application example, the effect of critical temperatures of organic fluids on the performance of Organic Rankine Cycles is successfully explained by the newly developed theory.